Potential Indications of Dupilumab in Th-2 Inflammatory Disease - Ilaria, Proietti; Nevena, Skroza; Ersilia, Tolino; Nicoletta, Bernardini; Federica, Trovato; Di Fraia, Marco; Agniezska, Dybala; Concetta, Potenza (Reviews on Recent Clinical Trials, 2024)
Dupilumab is a fully humanized IgG4 monoclonal antibody, inhibiting IL-4 and IL-13 signaling, which are the main cytokines involved in type 2 inflammatory diseases. Its introduction was a breakthrough in the treatment of moderate-to-severe atopic dermatitis, but it is also used in other inflammatory diseases, including asthma, eosinophilic esophagitis and chronic rhinosinusitis with nasal polyposis. Recent advances in the understanding of inflammatory pathways have revealed that Th2-type inflammation is involved in a wider range of diseases than previously thought. The aim of our review is to examine off-label therapeutic indications of dupilumab, including bullous dermatoses (pemphigus, bullous pemphigoid) and alopecia areata, and to investigate its potential applications in cancer patients on anti-PD1 therapy.
Keywords: atopic dermatitis